A search for an excited muon decaying to a muon and two jets in pp collisions at s√ = 8 TeV with the ATLAS detector - Aad, G. (2016)
A new search signature for excited leptons is explored. Excited muons are sought in the channel pp → µµ∗ → µµ jet jet, assuming both the production and decay occur via a contact interaction. The analysis is based on 20.3 fb−1 of pp collision data at a centre-of-mass energy of √ s = 8 TeV taken with the ATLAS detector at the Large Hadron Collider. No evidence of excited muons is found, and limits are set at the 95% confidence level on the cross section times branching ratio as a function of the excited-muon mass mµ ∗ . For mµ ∗ between 1.3 TeV and 3.0 TeV, the upper limit on σB(µ ∗ → µqq¯) is between 0.6 and 1 fb. Limits on σB are converted to lower bounds on the compositeness scale Λ. In the limiting case Λ = mµ ∗ , excited muons with a mass below 2.8 TeV are excluded. With the same model assumptions, these limits at larger µ ∗ masses improve upon previous limits from traditional searches based on the gauge-mediated decay µ ∗ → µγ